Synthesis and Characterization of Osmium Polycyclic Aromatic Complexes via Nucleophilic Reactions of Osmapentalyne. Issue 5 (20th December 2016) - Zhu, Qin; Zhu, Congqing; Deng, Zhihong; He, Guomei; Chen, Jiangxi; Zhu, Jun; Xia, Haiping
Abstract : Treatment of osmapentalyne [Os≡C‐C(COOMe)=CH‐C=CH‐C(PPh3 )=CH‐Cl(PPh3 )2 ] + B F 4 − with arylamines in the presence of Cs2 CO3 produced osmium‐bridged polycyclic aromatic complexes. In this reaction, metal carbyne of osmapentalyne was first attacked by nucleophiles, followed by a C‐H oxidative addition. The UV‐Vis spectra of these osmium‐bridged polycyclic aromatic complexes were measured. The result shows that these osmium‐bridged polycyclic aromatic complexes have broad absorption in the UV‐Vis region up to 650 nm. Abstract : Osmium polycyclic aromatic complexes, a series of metal‐bridged polycyclic aromatic complexes, in which the metal center was shared by three aromatic five‐membered rings, were constructed by the reactions of osmapentalyne with arylamines via the nucleophilic additionandaryl C‐H activation.